MeCP2 Epigenetic Silencing of Oprm1 Gene in Primary Sensory Neurons Under Neuropathic Pain Conditions - Sun, Na; Yu, Lina; Gao, Yibo; Ma, Longfei; Ren, Jinxuan; Liu, Ying; Gao, Dave Schwinn; Xie, Chen; Wu, Ying; Wang, Lieju; Hong, Juncong; Yan, Min (Frontiers in Neuroscience, 2021)
Opioids are the last option for the pharmacological treatment of neuropathic pain, but their antinociceptive effects are limited. Decreased mu opioid receptor (MOR) expression in the peripheral nervous system may contribute to this. Here, we showed that nerve injury induced hypermethylation of the Oprm1 gene promoter and an increased expression of methyl-CpG binding protein 2 (MeCP2) in injured dorsal root ganglion (DRG). The downregulation of MOR in the DRG is closely related to the augmentation of MeCP2, an epigenetic repressor, which could recruit HDAC1 and bind to the methylated regions of the Oprm1 gene promoter. MeCP2 knockdown restored the expression of MOR in injured DRG and enhanced the analgesic effect of morphine, while the mimicking of this increase via the intrathecal infusion of viral vector-mediated MeCP2 was sufficient to reduce MOR in the DRG. Moreover, HDAC1 inhibition with suberoylanilide hydroxamic acid, an HDAC inhibitor, also prevented MOR reduction in the DRG of neuropathic pain mice, contributing to the augmentation of morphine analgesia effects. Mechanistically, upregulated MeCP2 promotes the binding of a high level of HDCA1 to hypermethylated regions of the Oprm1 gene promoter, reduces the acetylation of histone H3 (acH3) levels of the Oprm1 gene promoter, and attenuates Oprm1 transcription in injured DRG. Thus, upregulated MeCP2 and HDAC1 in Oprm1 gene promoter sites, negatively regulates MOR expression in injured DRG, mitigating the analgesic effect of the opioids. Targeting MeCP2/HDAC1 may thus provide a new solution for improving the therapeutic effect of opioids in a clinical setting.